Compliance with International Humanitarian Law and Peacebuilding in Post-Conflict Kosovo - Alidemaj, Avni H.; Maliqi, Alban; Doone, Johne; Bytyci, Valdon (Hasanuddin Law Review, 2025)
Unprecedented violent conflicts occurred worldwide during the 20th century. Millions of lives lost, infrastructure destroyed, and generational effects on post-conflict nations. Meanwhile, international humanitarian law was developed to reduce conflict damage. Government parties to International Humanitarian Law (IHL) conventions have enforceable obligations to implement, promote, and perform their duties, helping to promote their wider recognition and enforcement. During the Kosovo conflict, Serbian military commanders and the police violated international humanitarian law by breaking fundamental precepts. The study of the Kosovo conflict prioritizes criminal accountability and historical documentation over the enduring societal consequences of violations of IHL. There are not many studies that look at how not following IHL affects transitional justice after a conflict. The findings indicate that successful post-conflict reconciliation necessitates enhanced domestic implementation and enforcement of transitional justice frameworks. This includes ensuring accountability for significant violations, fostering victim-centered truth, and institutionalizing IHL education to avert recurrence and facilitate enduring interethnic reconciliation. The article examines the major transgressions of IHL amidst the war in Kosovo (1998–1999), and their effects on post-conflict interethnic reconciliation. Utilizing qualitative, quantitative, and legal-dogmatic methods shows that non-adherence to IHL during armed conflict directly affects transitional justice and severely impacts reconciliation efforts.